A Reversibly Thermoresponsive, Theranostic Nanoemulgel for Tacrolimus Delivery to Activated Macrophages: Formulation and In Vitro Validation - Riddhi Vichare; Caitlin Crelli; Lu Liu; Amit Chandra Das; Rebecca McCallin; Fatih Zor; Yalcin Kulahci; Vijay S. Gorantla; Jelena M. Janjic (MDPI AG, 2023)
Despite long-term immunosuppression, organ transplant recipients face the risk of immune rejection and graft loss. Tacrolimus (TAC, FK506, Prograf®) is an FDA-approved keystone immunosuppressant for preventing transplant rejection. However, it undergoes extensive first-pass metabolism and has a narrow therapeutic window, which leads to erratic bioavailability and toxicity. Local delivery of TAC directly into the graft, instead of systemic delivery, can improve safety, efficacy, and tolerability. Macrophages have emerged as promising therapeutic targets as their increased levels correlate with an increased risk of organ rejection and a poor prognosis post-transplantation. Here, we present a locally injectable drug delivery platform for macrophages, where TAC is incorporated into a colloidally stable nanoemulsion and then formulated as a reversibly thermoresponsive, pluronic-based nanoemulgel (NEG). This novel formulation is designed to undergo a sol-to-gel transition at physiological temperature to sustain TAC release in situ at the site of local application. We also show that TAC-NEG mitigates the release of proinflammatory cytokines and nitric oxide from lipopolysaccharide (LPS)-activated macrophages. To the best of our knowledge, this is the first TAC-loaded nanoemulgel with demonstrated anti-inflammatory effects on macrophages in vitro.